Urban trees as sunlight control elements of vertical openings in front facades in sunny climates. Case study: Morus Alba on north façade - Villalba, Ayelén María (2014)
Benefits of urban trees are evident from the energy and environmental perspective, likewise they reduce glare and control light intensity. Given the hypothesis that trees reduce visible radiation significantly reaching lower level façades, this study is an approach to the analysis of urban forestation as a solar control element. The methodology employed involves measurement of: illuminance – transmittance variation, permeability variation and luminance contrast, by levels along the vertical development of the tree. Vertical illuminance values that exceed 25,000 lx were detected from 5.5 m onwards and values inferior to 3500 lx under that height. Based on the daily analysis of mulberry trees permeability variation in the visible spectrum, it is noted that incident radiation decreases by 90%, with 15% of variability. Natural light analysis must be differentiated by height since daylight scenarios vary accordingly.